Two new dactylogyrid species (Dactylogyroidea: Dactylogyridae), gill parasites of freshwater fishes from the Peruvian Amazon, including the proposal of Peruanella n. gen. - Cruces, Celso L.; Santillán, Luis A.; Silvera, Jordan F.; Morey, Germán Augusto Murrieta; Rubin, Veronica; Chero, Jhon D. (Zootaxa, 2024)
A new genus of dactylogyrid, Peruanella n. gen., is proposed to accommodate Peruanella madredediosensis n. sp. from Brachyplatystoma tigrinum (Britski) (Siluriformes: Pimelodidae) from the Madre de Dios River, in Puerto Maldonado City, Madre de Dios region, Peru. The new genus differs from Neotropical dactylogyrids by possessing a combination of the following features: (1) tandem gonads, (2) a tubular J-shaped MCO, (3) an accessory piece connected to the base of the MCO via a filament, (4) a midventral vaginal aperture, (5) anchors similar in shape, each with short roots, (6) straight and robust bars, and (7) equal hook, each with undilated shanks and a depressed thumb. A previously described species, Demidospermus aureagarciae Morey, Rojas, Dávila, Chu & De Pina, 2023 exhibits characteristics that are compatible with the diagnosis of the new genus; therefore, this species is transferred to the Peruanella n. gen. In addition, Jainus peruensis n. sp. is described from Brycon amazonicus (Spix & Agassiz) (Characiformes: Bryconidae). This new species, which is the first species of the genus described in Peru and the third species infecting a bryconid host, can be differentiated from all congeneric species due to: (1) a slender MCO forming a counterclockwise loop at the proximal end, (2) an unarticulated accessory piece with a scythe-shaped distal end, (3) a rod-shaped ventral bar with a medial projection, and (4) a V-shaped and grooved dorsal bar.